2006
DOI: 10.1038/nature05375
|View full text |Cite
|
Sign up to set email alerts
|

No supernovae associated with two long-duration γ-ray bursts

Abstract: 3It is now accepted that long duration γ-ray bursts (GRBs) are produced during the collapse of a massive star 1,2 . 11,12 . GRB 060505 was a faint burst with a duration of 4 s. GRB 060614 had a duration of 102 s and a pronounced hard to soft evolution. Both were rapidly localised by Swift's X-ray telescope (XRT). Subsequent follow-up of these bursts led to the discovery of their optical afterglows, locating them in galaxies at low redshift: GRB 060505 at z = 0.089 13 and GRB 060614 at z = 0.125 14,15 . The re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
443
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 425 publications
(453 citation statements)
references
References 31 publications
10
443
0
Order By: Relevance
“…Only a handful of such low luminosity events have been identified in the past decade, all of which have been relatively local (given the difficulty in observing low luminosity bursts beyond z ∼ 0.1). These include the well studied GRBsupernova pairs GRB 980425/SN 1998bw (Galama et al 1998), GRB 031203/SN 2003lw (Malesani et al 2004;Soderberg et al 2004), GRB 060218/SN 2006aj (Pian et al 2006) and GRB 100316D/SN 2010bh (Starling et al 2011;Cano et al 2011), and the enigmatic GRBs 060505 and 060614, where associated SNe have been ruled out to deep limits, and whose origin remains mysterious (Fynbo et al 2006;Della Valle et al 2006). They may be low luminosity events akin to those above, but where the SNe is absent (e.g.…”
Section: Burst Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a handful of such low luminosity events have been identified in the past decade, all of which have been relatively local (given the difficulty in observing low luminosity bursts beyond z ∼ 0.1). These include the well studied GRBsupernova pairs GRB 980425/SN 1998bw (Galama et al 1998), GRB 031203/SN 2003lw (Malesani et al 2004;Soderberg et al 2004), GRB 060218/SN 2006aj (Pian et al 2006) and GRB 100316D/SN 2010bh (Starling et al 2011;Cano et al 2011), and the enigmatic GRBs 060505 and 060614, where associated SNe have been ruled out to deep limits, and whose origin remains mysterious (Fynbo et al 2006;Della Valle et al 2006). They may be low luminosity events akin to those above, but where the SNe is absent (e.g.…”
Section: Burst Propertiesmentioning
confidence: 99%
“…Watson et al 2011;Starling et al 2011). Low redshift bursts include several which are sub-luminous, such as GRBs 090825 and 031203 (Galama et al 1998;Malesani et al 2004;Soderberg et al 2004), and others such as GRBs 060505 and 060614 that were long bursts without associated supernovae (Fynbo et al 2006;Della Valle et al 2006). Cross-correlation with local galaxy surveys (at z < 0.037) has suggested that some low redshift GRBs in the existing burst catalogues have yet to be identified as such (Chapman et al 2007) and hence opportunities to study their properties in detail have been missed.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in figure 1, the constraints on GRB 060505 and GRB 060614 are about as constraining as the those related to the short gamma-ray bursts discussed earlier. These puzzling systems may be related to non-56 Ni-producing supernovae or they may be merger gamma-ray bursts with longer durations than usually found [41][42][43][44][45].…”
Section: Supernova-less Gamma-ray Burstsmentioning
confidence: 99%
“…In contrast, "non-SN GRBs" (or dark HNe) have also been discovered (GRBs 060605 and 060614) (Fynbo et al 2006, Gal-Yam et al 2006, Della Valle et al 2006, Gehrels et al 2006. Upper limits to brightness of the possible SNe are about 100 times fainter than SN 1998bw.…”
Section: Introductionmentioning
confidence: 99%